2020
DOI: 10.1080/26410397.2020.1722404
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to care-seeking among survivors of gender-based violence in the Dadaab refugee complex

Abstract: In humanitarian settings, timely access to care is essential for survivors of gender-based violence (GBV). Despite the existence of GBV support services, challenges still exist in maximising benefits for survivors. This study aimed to understand the characteristics of violence against women and explore barriers and facilitators to care-seeking for GBV by women in two camps within the Dadaab refugee complex in Kenya. A mixed-methods design was used to study women accessing comprehensive GBV services between Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 12 publications
2
37
1
Order By: Relevance
“…Task-sharing is one strategy that can be used to improve acceptability, accessibility and scale-up of services to refugee survivors of violence in a camp context. 35 36 Further evaluation of preventive programmes which engage the community or intimate partners must also be undertaken to understand the most effective approach to tackling harmful normative beliefs that perpetuate further violence. 37…”
Section: Discussionmentioning
confidence: 99%
“…Task-sharing is one strategy that can be used to improve acceptability, accessibility and scale-up of services to refugee survivors of violence in a camp context. 35 36 Further evaluation of preventive programmes which engage the community or intimate partners must also be undertaken to understand the most effective approach to tackling harmful normative beliefs that perpetuate further violence. 37…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60][61] The vulnerability of women in refugee and IDP camps to SGBV is predetermined by pre-existing cultural gender inequalities and domestic violence and deterioration of traditional gender roles in society due to the destruction of households as a result of war and deaths of family members. 34,[62][63][64][65][66][67] Peacekeepers and aid workers have engaged in hegemonic masculinity practices that encourage sexual exploitation and abuse of the most marginalized in the communities -women and children. 68,69 The harm suffered by survivors has hardly been addressed by any of the agencies, including the United Nations.…”
mentioning
confidence: 99%
“…Women with more severe physical or cognitive disabilities did not access the GBV services, suggesting that they may have faced challenges getting to theservices. All women enrolled in the cohort study reported challenges accessing services, especially due to the on-going camp closure and repatriation processes that were underway during the cohort study (Hossain et al ., 2018; Muuo et al ., 2020). Therefore, it is feasible that women with more severe disabilities faced significant difficulties accessing GBV response services within the camp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to response services, the GBV support centres also provided outreach and camp-based violence prevention activities. Additional details on the GBV services are available elsewhere (Hossain et al ., 2018; Izugbara et al ., 2018; McAlpine et al ., 2020; Muuo et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%